"Crime Has No Chance": The Discourse of Everyday Criminality in the East German Press, 1961–1989. Issue 1 (31st March 2017) - Millington, Richard
Abstract: According to Friedrich Engels, communists would "take an axe to the root of crime." Criminality was, in this and similar views, "alien" to the very essence of prevailing social conditions in communist societies and ought to have disappeared as a phenomenon as soon as socialism was established. Yet, despite the ruling Socialist Unity Party's (SED) claim to have created "really existing socialism" in East Germany, crime existed and persisted. Official statistics showed that over one hundred thousand incidents of "everyday" criminal offenses, such as theft, were recorded annually. The SED regarded public relations work concerning criminality as essential to its prevention. This article examines the narrative of crime that appeared in the pages of the East German magazine Neue Berliner Illustrierte, which, following SED instructions, attempted to shape public perceptions by informing readers that crime rates were decreasing and that no serious crimes were taking place. Moreover, the articles made it clear that the only way to eliminate the causes of crime were for citizens to live according to the socialist tenets set forth by the party. As this suggests, the regime used the media and its treatment of crime and criminality in an attempt to win greater legitimacy and coopt citizens for the socialist project. Abstract : Kommunistischen Ideologen zufolge war Kriminalität dem eigentlichen Wesen vorherrschender Bedingungen in staatssozialistischen Gesellschaften „fremd" und hätte als Phänomen verschwinden müssen, sobald der Sozialismus etabliert worden war. Doch entgegen der Behauptungen der SED, den „real existierenden Sozialismus" erschaffen zu haben, existierte Verbrechen nach wie vor in der DDR. Offizielle Statistiken registrierten mehr als einhunderttausend Vorfälle „alltäglicher" Kriminalität, wie etwa Diebstahl. Dieser Artikel konzentriert sich auf Schilderungen von Verbrechen, die in dem beliebten ostdeutschen Magazin Neue Berliner Illustrierte ( NBI ) erschienen, und zeigt wie die SED versuchte die öffentliche Wahrnehmung zu beeinflussen, indem die Auffassung verbreitet wurde, dass die Kriminalitätsraten sanken und keine schweren Verbrechen stattfanden. Darüber hinaus hoben die NBI Artikel hervor, dass der einzige Weg, die Ursachen von Verbrechen zu eliminieren, darin bestand, gemäß der von der Partei vorgegebenen Grundsätze zu leben. Basierend auf diesen Erkenntnissen argumentiert dieser Aufsatz generell, dass das Regime die Medien und deren Darstellung von Verbrechen und Kriminalität benutzte, um größere Legitimität für sich zu gewinnen und seine Staatsbürger so für das sozialistische Projekt zu kooptieren.